Strategic Sustainable Management for Water Transmission System: A SWOT-QSPM Analysis - Ni Made Sumiarsih; Djoko Legono; Robert J. Kodoatie (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2018)
In general, the problem of a water resources infrastructure, especially the raw water transmission system, is that the actual discharge is not in accordance with design discharge because of water losses along the transmission system.To restore the capacity to the design discharge, a comprehensive strategy is required. Various strategy methods have been developed especially the strategy of managing a system. This paper discusses how to analyze the comprehensive strategy with system component approach for water transmission system. The research used Klambu-Kudu Water Transmission System in Semarang, Central Java, Indonesia as a case study. Strategy analysis of Klambu-Kudu Water Transmission System utilized the modified Strength, Weakness, Opportunity, and Threats (SWOT) with Likert scale and Quantitative Strategic Planning Matrix (QSPM) method. SWOT analysis is was carried out to obtain a comprehensive strategy on each component of the water transmission system (intake, mud pouch, siphon, gutter, bridge, culvert, regulator doors, suppletion, drain pipe, and / or excavation), while the QSPM method is required to analyze the strategic priorities of component of Klambu Kudu Water Transmission System. Key factors of water transmission system performance were obtained from the discussion of experts, the management of Klambu Kudu Water Transmission System and the community. The results are a priority of strategies which are dominated by the opportunity factors to solve the problem of weakness (operation and maintenance, sedimentation, damage) and threats (water theft, destruction of buildings, flood) as well as maximizing the strengths (condition of the component, function, accessibility).